Teachers’ Beliefs And Practices In Applying Learning Management System Aksara (LMSA) For E-Learning - Iwan Iwan; Muhammad Asfah Rahman; Andi Hamzah Fansury (Postgraduate Bosowa University, 2023)
The research aimed at describing how Teachers’ Beliefs and Practices in Applying Learning Management System Aksara (LMSA) For E-Learning. In order to achieve the aims, the researcher designed three main objectives: to find out how is teachers’ belief in applying Learning Management System Aksara (LMSA) for e-learning, how is teachers’ practice in applying Learning Management System Aksara (LMSA) for e-learning and analysing some discrepancies between teachers’ beliefs and practices in applying Learning Management System Aksara (LMSA) for e-leraning. The researcher applied the mix method. The samples were chosen purposively from 30 teachers at Universitas Bosowa. The data analyzed was in quantitative and qualitative research involved analyzing and observing data dependably and accurately. The result of questionnaire showed that the that the teachers’ are firmly believes that LMSA Unibos can be apllied for e-learning at Universitas Bosowa. The result of observation related to the teachers’ practices in applying LMSA Unibos for e-learning at Universitas Bosowa shown that most of the respondents’ do not active in using LMSA unibos in each meeting for E-Learning. In other words, we can conclude that only a few respondents use LMS Aksara Unibos for E-Learning process at Bosowa University. After comparing both data, the reseracher concluded there are discrepancies or gap between teachers’ beliefs and practices in applying LMSA Unibos for e-learning, for the reason that questionnaire result classified as a very high level of teachers’ believes that LMSA Unibos can be apllied for e-learning at Universitas Bosowa but observation result found that most of respondents who have answered the questionnaire do not uploaded their learning material into their LMS Aksara account. In other words, the process of using applying LMSA Unibos for e-learning in the learning process at Universitas Bosowa is not optimal